Pedagogia da terra: olhar dos/as educandos/as em relação à primeira turma do estado de São Paulo - Amaral, Débora Monteiro do (2010)
The present research investigated the point of view of the scholars from the course of Land Pedagogy at UFSCar (Federal University of São Carlos) about this course, which is, the first one in the State of São Paulo. This course began in the second semester of 2007 at this University and has the participation of students from settlements and camps in several cities in the State of São Paulo, the ones who belong to four different social movements: Movement of Rural Landless Workers (Movimentos dos Trabalhadores Rurais Sem Terra MST), Federation of Rural Salaried Farmers in the State of São Paulo (Federação dos Agricultores Rurais Assalariados de São Paulo FERAESP), Federation of Familiar Agriculture in the State of São Paulo (Federação da Agricultura Familiar do Estado de São Paulo FAF) and Organization of Settled Women and Quilombolas* in the State of São Paulo (Organização das Mulheres Assentadas e Quilombolas do Estado de São Paulo - OMAQUESP). The course started by having sixty students and has now (fourth stage), forty-three, being, out of this, thirty-nine women and four men. The course of Land Pedagogy is a course that came to exist due to the demand and claim of social movements and through partnerships with the National Institute of Colonization and Land Reform Institute (Instituto Nacional de Colonização e Reforma Agrária INCRA) along with UFSCar and through the National Program of Education as for Land Reform (Programa Nacional de Educação na Reforma Agrária PRONERA), what made it viable to organize as well as implement it in the state. The course of Land Pedagogy has as methodology the alternation pedagogy, with organizes the learning process of scholars in two different periods of time: the school-time, at which presential classes take place and communitytime, through practical activities and researches developed in the communities from which the scholars come. Based on this context the research brings along as main concepts the educational processes that occur in these communities, that is, the teaching and learning based on Paulo Freire s pedagogy, the disclosure of the land social movements and land education as far as the differentiation of rural education is concerned. In order to make it viable, we relied, as methodological and theoretical basis, on the purposes of the participating research, guided by Carlos Rodrigues Brandão s (1985, 2006) as well as Paulo Freire s (1983, 1992) elaborations. Three men and thirteen women from different settlements and of different ages and social movements took part in the study. The gathering of data relied on the collecting of bibliographical facts, general interviews, scouts, talks, observations, by accompanying the scholars at their school-time and community-time and notes in the field diary. The analysis of the data occurred in a shared way and based on the following categories: 1) Interdiction; 2) Otherness and 3) Solidarity. The data showed that the interdiction processes the scholars went through along their lives made it possible the creation of forms of resistance and overcoming of this question while mobilizing through their social movements and learn from these processes. It s noticeable that they learn along with and from the differences, being these cultural, generational and ideological ones, among others. It s also perceivable the solidarity, cooperation and collaboration as factors that along with the group, made it possible this course to exist. The alternation system enabled the indissolubility between practice and theory but hampered with the interaction among the students who attend the course and the university community. It becomes necessary the creation of spaces in which everybody from this community gets to know one another and dialogue about the course so that they can know how to respect one another and through dialogue to teach and to learn.